Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd003331.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise based rehabilitation for heart failure

Abstract: Background The prevalence of chronic heart failure is increasing, and increases with increasing age. Major symptoms include breathlessness and restricted activities of daily living due to reduced functional capacity, which in turn affects quality of life. Exercise training has been shown to be effective in patients with coronary heart disease and has been proposed as an intervention to improve exercise tolerance in patients with heart failure. Objectives To determine the effectiveness of exercise based inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
204
4
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(231 citation statements)
references
References 77 publications
18
204
4
5
Order By: Relevance
“…; work capacity: +14 W and 6-MWD: +52 m) is similar to the results of the recent Cochrane review on CR in adults of all ages with CHF [15]. In this analysis of 29 randomised controlled trials of exercise-based interventions with a total of 1126 patients, compared with usual medical care or placebo, peak VO 2 improved by 2.2 ml/kg/min (95% CI 2.8-1.5), work capacity by 15 W (95% CI and distance on the six minute walk test by 41 m (95% CI 65-17).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…; work capacity: +14 W and 6-MWD: +52 m) is similar to the results of the recent Cochrane review on CR in adults of all ages with CHF [15]. In this analysis of 29 randomised controlled trials of exercise-based interventions with a total of 1126 patients, compared with usual medical care or placebo, peak VO 2 improved by 2.2 ml/kg/min (95% CI 2.8-1.5), work capacity by 15 W (95% CI and distance on the six minute walk test by 41 m (95% CI 65-17).…”
Section: Discussionsupporting
confidence: 87%
“…Modern management of patients with heart failure implies a multidisciplinary ap-proach with optimisation of medical treatment, risk factor intervention, teaching, exercise advice and training, as well as tailored psychosocial support [11]. This approach is expected to lead to a reduction of rehospitalisation rates [12], costs [13] and even mortality [14], although the latter is still debated [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, the effects of exercise training on clinical outcomes are not well identified. Moreover, only 3 studies to date have followed patients beyond 6 months, 3,5,6 leaving the role of exercise in HF unclear.…”
mentioning
confidence: 99%
“…In this study, the increased 6MWT distance could be observed in both groups, but the 6MWT distance in IG after intervention was significantly higher than in CG after observation. A meta-analysis which was performed by Rees et al [21] revealed that the 6MWT distance increased by 40.9 metres, and a study by Arad et al [20] revealed a 39% improvement of 6MWT distance after exercise training for 18 weeks.…”
Section: Discussionmentioning
confidence: 99%